ANALISA KEKUATAN KONSTRUSKI DOUBLE BOTTOM KAPAL AKIBAT PERUBAHAN UKURAN MANHOLE SEBAGAI UPAYA UNTUK MENINGKATKAN KESELAMATAN PELAYARAN DI ALKI II - Jamal Ikhwani, Rodlian; Hariyono, Hariyono; Mujib Syadzali, Abdul; Alamsyah, Alamsyah; Syahab, Husein (Construction and Material Journal, 2025)
This study analyzes the strength of the ship's double bottom construction due to changes in manhole size to improve shipping safety in Indonesian Archipelagic Sea Lane II (ALKI II). The study was conducted at Taboneo Anchorage, South Kalimantan, which is a busy shipping route. The initial stage includes measuring the ship's structure and tidal data, as well as collecting secondary data in the form of construction drawings and material specifications for General Cargo type ships. Next, structural modeling was carried out using the Finite Element Method (FEM) approach with reference to Indonesian Classification Bureau (BKI) Rules 2025. The cargo load and bottom load were calculated and input into the model. Three variations of manhole sizes were tested: 350 x 450 mm, 400 x 600 mm, and 400 x 800 mm. The simulation results show that at 350 x 450 mm, the maximum stress is 111.23 N/mm² and the displacement is 4.9 mm, still safely below the BKI permit limit (150 N/mm²). At a size of 400 x 600 mm, the stress increases to 124.68 N/mm² with a displacement of 5.32 mm, which remains safe and recommended. However, the size of 400 x 800 mm produces a stress of 283.23 N/mm² and a displacement of 9.79 mm, exceeding the allowable limit and thus risking structural failure. The maximum recommended manhole size is 400 x 600 mm to maintain construction strength and navigation safety in ALKI II.